2014
DOI: 10.1002/pmic.201300443
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation dynamics of membrane proteins from Arabidopsis roots submitted to salt stress

Abstract: An excess of NaCl in the soil is detrimental for plant growth. It interferes with mineral nutrition and water uptake and leads to accumulation of toxic ions in the plant. Understanding the response of roots to NaCl stress may facilitate the development of crops with increased tolerance to this and other stresses. Since controls achieved at the posttranslational level are of critical importance for regulating protein function, the present work used a robust label-free quantitative proteomic methodology to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 78 publications
1
26
1
Order By: Relevance
“…Thus, we hypothesize that a reduced physical interaction between PLD␦ and PIP2;1 upon H 2 O 2 treatment would result in a decreased PA binding to PIP2;1, thereby altering PIP2;1 function. Such a role for lipid signaling in PIP2;1 function is consistent with the suggested role of lipid-mediated signaling in the transduction of stress signals arising from the soil (89).…”
Section: Table II Characterization Of Fret Interaction Between Feronisupporting
confidence: 64%
“…Thus, we hypothesize that a reduced physical interaction between PLD␦ and PIP2;1 upon H 2 O 2 treatment would result in a decreased PA binding to PIP2;1, thereby altering PIP2;1 function. Such a role for lipid signaling in PIP2;1 function is consistent with the suggested role of lipid-mediated signaling in the transduction of stress signals arising from the soil (89).…”
Section: Table II Characterization Of Fret Interaction Between Feronisupporting
confidence: 64%
“…The authors also demonstrate that the PM proteins are the target of different protein kinases in response to NaCl stress, and also point out to an important role for lipid signaling in salt stress responses in plants. Other PM proteins that have been shown to be upregulated under salt stress, and correlate with salt tolerance are aquaporins (Mansour, 2014, Vialaret et al, 2014. Aquaporins are mainly involved in water absorption under salinity.…”
Section: The Pm Proteins and Salt Tolerancementioning
confidence: 98%
“…This results in enhancing the activity of the PM Na + /H + antiporter of salt adapted cells; Na + /H + antiporters are known to play a key role in Na + exclusion under high salt. Vialaret et al (2014) identified PM proteins from Arabidopsis roots that upregulated in response to NaCl treatment. These proteins include PM transport proteins and protein kinases, which are involved in ion homeostasis and signal perception.…”
Section: The Pm Proteins and Salt Tolerancementioning
confidence: 98%
See 1 more Smart Citation
“…The N & C-terminals of NRT2.1 contain many protein kinase recognition motifs. Like NRT1.1, NRT2.1 is regulated by a phosphorylation/dephosphorylation mechanism under high nitrogen conditions [377] [378] NRT2.1 gene expression is induced by light and sugars. Sugar and nitrate are coupled by glucose metabolism by oxidative pentose phosphate pathway (OPPP) [379].…”
Section: Regulation Of Nitrogen Uptakementioning
confidence: 99%